2012
DOI: 10.1002/jat.2741
|View full text |Cite
|
Sign up to set email alerts
|

Hair testing for cocaine and metabolites by GC/MS: criteria to quantitatively assess cocaine use

Abstract: A simple, rapid and sensitive method has been developed and validated for the determination of cocaine and its main metabolites (benzoylecgonine and cocaethylene) in human hair. The method involved solid-phase extraction with an Oasis HLB extraction cartridge and subsequent analysis by GC/MS. The limit of detection was 0.01 ng mg(-1) for cocaine, 0.04 for benzoylecgonine and 0.03 for cocaethylene. The method validation included linearity (with a correlation coefficient >0.99 over the range 0.2-50 ng mg(-1) ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Our data concur with hair testing studies that reported lower levels of BEG than COC 13, 17, 19. The basic drug COC has a greater affinity for melanine than for BEG, its amphoteric metabolite 19.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our data concur with hair testing studies that reported lower levels of BEG than COC 13, 17, 19. The basic drug COC has a greater affinity for melanine than for BEG, its amphoteric metabolite 19.…”
Section: Resultssupporting
confidence: 91%
“…COC levels were above 0.5 ng/mg (ranging from 1.63 to 39.29 ng/mg) in all samples. Mean COC concentration was 9.49 ng/mg, indicating that most patients used COC regularly 13, 19. BEG levels, which were determined in all hair samples, were above 0.05 ng/mg (ranging from 0.19 to 5.77 ng/mg, mean value 1.40).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Instrument analysis methods involve high performance liquid chromatography (HPLC) [3], liquid chromatography-mass spectrometry (LC-MS) [4,5], gas chromatography-mass spectrometry (GC-MS) [6,7], and capillary electrophoresis-mass spectrometry (CE-MS) [8], etc. These methods are highly sensitive and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Por se tratar de um composto naturalmente anfótero, a benzoilecgonina é comumente extraída pela técnica de SPE, especialmente por cartuchos de fase mista que permitem tanto a sua extração quanto da própria cocaína e outros produtos de biotransformação (ALESKA et al, 2012;MUSSHOFF et al, 2009;LÓPEZ-GUARNIDO et al, 2013;GOUVEIA et al, 2012;BARROSO et al, 2008). Embora a técnica de extração por SPE seja amplamente utilizada, técnicas miniaturizadas como a LPME e a SPME são a tendência atual, como já mencionado (BACIU et al, 2015).…”
Section: Confirmação De Benzodiazepínicos Por Gc-msunclassified